Enhancing growing rabbit heat stress resilience through dietary supplementation with natural antioxidants - Ibrahim Talat El-Ratel; Aml Mekawy; Sara H.M. Hassab; Sameh Abdelnour (BMC Veterinary Research)
Abstract Animal husbandry development is influenced by various factors, with heat stress (HS) being a significant factor. The aim of this experiment was to explore the potential of natural antioxidants such as vitamin C (VITC), vitamin E (VITE), lycopene (LYC), and allicin (AL) in enhancing growth, immune function and maintaining the redox status of fattening rabbits under HS. Male weaning rabbits (n = 150, 5 weeks of age) were randomly assigned to 5 groups. The rabbits were fed a basal diet (control group) or supplemented with 40 mg of vitamin E (VE40), 5 mg of vitamin C (VC5), 150 mg of lycopene (LYC150), or 150 mg of allicin (AL150) per kg of diet, respectively, under summer Egyptian conditions. The overall temperature humidity index (THI) value was 29.76, indicating severe HS during the experimental period. The findings indicated that all dietary supplemented groups showed significant improvements in live body weight at 8 weeks (P < 0.0001) and 11 weeks (P < 0.05) of age compared to the control group. The feed conversion ratio (FCR) was improved with all additives (P < 0.05), while feed intake and carcass traits were not affected by the treatments (P > 0.05). The AL group had the highest dressing percentage compared to the other groups (P < 0.05). Feeding stressed rabbits with antioxidant supplements resulted in a higher hemoglobin concentration compared to the control group (P < 0.05). Aspartate transaminase (AST), triglycerides, and creatinine levels were decreased with all additives as compared to the control group (P < 0.05). Total protein and albumin were significantly higher in AL group than in other groups (P < 0.05). The serum Immunoglobulin G (IgG) was significantly increased, while tumor necrosis factor alpha (TNF-α), interleukin-4 (IL-4), and interferon gamma (IFN-γ) were decreased by all feed additives (P < 0.05). Immunoglobulins (IgA and IgM) did not differ among all experimental groups (P > 0.05). Serum total antioxidant capacity (TAC) and glutathione (GSH) levels were higher in all supplement groups compared to the HS group (P < 0.05). All dietary supplements significantly reduced malondialdehyde (MDA) levels in liver tissues and blood serum compared to the control group (P < 0.05). Collectively, allicin emerged as a potent shield against heat stress, bettering lycopene and vitamins E and C in safeguarding the well-being of growing rabbits.